Analysis of the Phytochemical Performance of the Neem Plant (Azadirachta indica) Sumbawa Phenotype as a Natural Insecticide - Azis, Abdul; Syazali, Muhammad; Chaidir, Riri Rimbun Anggih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Excessive use of chemical insecticides on plants has had a negative impact on the environment and human health. To overcome this, the use of plant-based pesticides is an attractive alternative, but not yet fully optimal in Indonesia. This research aims to study the potential use of neem leaf extract (Azadirachta indica) as a plant insecticide, with a focus on local knowledge of the Samawa tribe on Sumbawa Island. Extraction methods and phytochemical analysis were carried out, as well as insecticidal power tests against several common pest species in the area. The research results show that neem leaf extract has the potential to be an effective natural insecticide in controlling pest populations. Factors such as extract concentration and drying method of neem leaves influence its effectiveness. The use of neem leaf extract at a dose of 80 gr/liter has proven to be more effective than the Dane brand of vegetable pesticide at three times the dose. However, the use of synthetic pesticides at the recommended dosage still shows faster and more effective results in controlling pests. This research contributes to the development of environmentally friendly and effective plant protection materials, and expands understanding of the potential of local natural resources for sustainable agriculture.